The “Phrases without (Con-)text” in the Soviet Propaganda (1920–1940) - Shvetsova, Maria (Populismo y propaganda: entre el presente y el pasado, 2020)
In the present paper we are trying to reconsider the role of the phrases without (con-)text in the totalitarian discourse by proposing a classification based on the corpus of the Soviet propaganda. The present research is based on the theory of detachable/detached aphorisations of Dominique Maingueneau. Among them we distinguish the following groups: proverbs, quotations, slogans, slogans of the propaganda posters, headings and crossheadings of the press.